The Fiore ; and, the Detto d'amore : a late 13th-century Italian translation of the Roman de la Rose, attributable to Dante - Dante Alighieri, 1265-1321; Casciani, Santa; Kleinhenz, Christopher (William and Katherine Devers series in Dante studies, 2011)
"This is the first English translation of Il Fiore, the late-thirteenth-century narrative poem in 232 sonnets based on the Old French Roman de la Rose, and the Detto d'Amore, a free-wheeling version of many Ovidian precepts of love in 240 rhymed couplets. The elaborate allegory of the Fiore presents the complex workings of love, understood primarily as carnal passion, in the human psyche through the use of personifications of a wide array of characters who engage in various social (and bellic) interactions. There are personifications of social stereotypes and attitudes, mythological figures, abstract qualities, psychological and physical states, and personality traits."